2018
DOI: 10.1093/ejcts/ezy066
|View full text |Cite
|
Sign up to set email alerts
|

Samurai cannulation (direct true-lumen cannulation) for acute Stanford Type A aortic dissection†

Abstract: Early outcomes of the initial series of surgery for Stanford Type A aortic dissection with Samurai cannulation was favourable with acceptable mortality and stroke rates without cannulation-related complications. Samurai cannulation represents an easy, safe and reasonable option for cardiopulmonary bypass in surgery for acute Stanford Type A aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Recently, Kitamura et al conducted a similar comparison and reported reasonable stroke and mortality rates and no cannulation complications. 8 Group-A and B specific mortality was estimated to be 10% vs 30% and morbidity was (44.4% vs 57.1%), however, no statistical group difference was detected.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recently, Kitamura et al conducted a similar comparison and reported reasonable stroke and mortality rates and no cannulation complications. 8 Group-A and B specific mortality was estimated to be 10% vs 30% and morbidity was (44.4% vs 57.1%), however, no statistical group difference was detected.…”
Section: Discussionmentioning
confidence: 81%
“…6,7 Yamamoto and Kitamura et al's comparison between direct TLC and other cannulation strategies reported no cannulation complications along with reasonable mortality and stroke rates. 8,9 Along with the scarcity of literature on aortic dissection in Pakistan, this new technique has only been recently introduced in the country at Aga Khan University Hospital. No study is available in Pakistan on this subject, while only sparse comparisons have been made worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods to identify the true lumen included transesophageal echocardiography [26] or epiaortic ultrasound, but were time-consuming in emergency conditions or in the presence of circumferential aortic dissection or true lumen collapse [27]. Nevertheless, DTLC was shown to be safe and effective in patients with A-AAD [4,6,7,28,29], and restoring antegrade CPB perfusion was possible despite the complexity of the existing clinical scenarios, such as true lumen collapse, infrarenal aneurysm, peripheral vascular disease or obesity [6].…”
Section: Plos Onementioning
confidence: 99%
“…Die Aorta kann auch direkt unter Sicht eröffnet und kanüliert werden [8]. Da die Aorta jedoch am unvorbereiteten, ungekühlten Patienten eröffnet wird, ist das Komplikationsrisiko als potenziell hoch einzustufen.…”
Section: Merkeunclassified